Hydrological effects of large dams in Chilean rivers - Luisa Villablanca; Ramon J. Batalla; Gemma Piqué; Andrés Iroumé (Journal of Hydrology: Regional Studies, 2022)
Study region: Eight rivers regulated by large dams located in three hydro-climatic zones along the Chilean latitudinal gradient. Study focus: We performed a multi-temporal scale analysis of flow records and we used data from official gauging stations to characterise the non-altered and the altered river regimes to determine the magnitude and persistence of the hydrological alteration downstream from large dams in Chile. These analyses provide relevant information to improve the understanding of such alterations, and a conceptual basis for assessing future impacts as the country plans to build a series of large dams in the coming years. New hydrological insights for the region: The mean annual runoff was reduced in all the study rivers. The monthly flows of the rivers from the northern arid zone were the most affected by the dams. The magnitude and frequency of floods decreased in all the study rivers. Moreover, northern drier river systems did not recover their hydrological conditions in the distance downstream of the dams, probably due to transmission losses and water extractions and diversions; in contrast, southern rivers partially recovered their flow regimes with distance downstream, mainly due to the inflows from permanent non-regulated tributaries. So far, this is the first study in Chile that comprehensively analyses the hydrological effects of large dams.